Ultrafast electric control of cavity mediated single-photon and photon-pair generation with semiconductor quantum dots - Bauch, David; Heinze, Dirk Florian; Förstner, Jens; Jöns, Klaus; Schumacher, Stefan (Physical Review B)
Employing the ultrafast control of electronic states of a semiconductor quantum dot in a cavity, we introduce an approach to achieve on-demand emission of single photons with almost perfect indistinguishability and photon pairs with near ideal entanglement. Our scheme is based on optical excitation off resonant to a cavity mode followed by ultrafast control of the electronic states using the time-dependent quantum-confined Stark effect, which then allows for cavity-resonant emission. Our theoretical analysis considers cavity-loss mechanisms, the Stark effect, and phonon-induced dephasing, allowing realistic predictions for finite temperatures.
Keywords: tet_topic_qd

Nondegenerate two-photon absorption in ZnSe: Experiment and theory - Krauss-Kodytek, L.; Hannes, W.-R.; Meier, Torsten; Ruppert, C.; Betz, M. (Physical Review B)

Nondegenerate two-photon absorption in ZnSe: Experiment and theory - Krauss-Kodytek, L.; Hannes, Wolf-Rüdiger; Meier, Torsten; Ruppert, C.; Betz, M. (Physical Review B)

Split-ring polariton condensates as macroscopic two-level quantum systems - Xue, Yan; Chestnov, Igor; Sedov, Evgeny; Kiktenko, Evgeniy; Fedorov, Aleksey K.; Schumacher, Stefan; Ma, Xuekai; Kavokin, Alexey (Physical Review Research)

Structuring coflowing and counterflowing currents of polariton condensates in concentric ring-shaped and elliptical potentials - Barkhausen, Franziska; Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Nonlinear Bicolor Holography Using Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Cinchetti, Mirko; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)

Formation dynamics of exciton-polariton vortices created by nonresonant annular pumping - Berger, Bernd; Schmidt, Daniel; Ma, Xuekai; Schumacher, Stefan; Schneider, Christian; Höfling, Sven; Assmann, Marc (Physical Review B)

Accurate photon echo timing by optical freezing of exciton dephasing and rephasing in quantum dots - Kosarev, Alexander N.; Rose, Hendrik; Poltavtsev, Sergey V.; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (Communications Physics)
Abstract Semiconductor quantum dots are excellent candidates for ultrafast coherent manipulation of qubits by laser pulses on picosecond timescales or even faster. In inhomogeneous ensembles a macroscopic optical polarization decays rapidly due to dephasing, which, however, is reversible in photon echoes carrying complete information about the coherent ensemble dynamics. Control of the echo emission time is mandatory for applications. Here, we propose a concept to reach this goal. In a two-pulse photon echo sequence, we apply an additional resonant control pulse with multiple of 2 π area. Depending on its arrival time, the control slows down dephasing or rephasing of the exciton ensemble during its action. We demonstrate for self-assembled (In,Ga)As quantum dots that the photon echo emission time can be retarded or advanced by up to 5 ps relative to its nominal appearance time without control. This versatile protocol may be used to obtain significantly longer temporal shifts for suitably tailored control pulses.

k.p-based multiband simulations of non-degenerate two-photon absorption in bulk GaAs - Hannes, Wolf-Rüdiger; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXIV)

Strongly nonresonant four-wave mixing in semiconductors - Hannes, W.-R.; Trautmann, Alexander; Stein, M.; Schäfer, F.; Koch, M.; Meier, Torsten (Physical Review B)

Enhanced high-order harmonic generation in semiconductors by excitation with multicolor pulses - Song, Xiaohong; Yang, Shidong; Zuo, Ruixin; Meier, Torsten; Yang, Weifeng (Physical Review A)

Realization of all-optical vortex switching in exciton-polariton condensates - Ma, Xuekai; Berger, B; Aßmann, M; Driben, R; Meier, Torsten; Schneider, C; Höfling, S; Schumacher, Stefan (Nature Communications)

Efficient Bosonic Condensation of Exciton Polaritons in an H-Aggregate Organic Single-Crystal Microcavity. - Ren, J; Liao, Q; Huang, H; Li, Y; Gao, T; Ma, Xuekai; Schumacher, Stefan; Yao, J; Bai, S; Fu, H (Nano Letters)

Topological edge states of nonequilibrium polaritons in hollow honeycomb arrays. - Ma, Xuekai; Kartashov, YV; Ferrando, A; Schumacher, Stefan (Optics Letters)

Multistable circular currents of polariton condensates trapped in ring potentials. - Barkhausen, F; Schumacher, Stefan; Ma, Xuekai (Optics Letters)

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

Circular polarization reversal of half-vortex cores in polariton condensates - Pukrop, Matthias; Schumacher, Stefan; Ma, Xuekai (Physical Review B)

Spiraling vortices in exciton-polariton condensates - Ma, Xuekai; Kartashov, Yaroslav V.; Gao, Tingge; Torner, Lluis; Schumacher, Stefan (Physical Review B)

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)